2023
DOI: 10.1002/srin.202200940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transversal Temperature Distribution and Phase State on Strip Profile During Hot Rolling Process

Abstract: Transversal temperature distribution and phase transformation of the strip steel in hot rolling process are analyzed by thermographic observations and thermal simulation tests. The effects of transversal temperature distribution and phase state on strip profile are investigated by finite element (FE) simulations, in which the material model of the strip steel is generated from the thermal simulation tests and a constitutive model. FE calculation shows that the decreased temperature at the edge causes smaller s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The steel industry, as a large-scale and complex process industry, has the characteristics of multivariate, strong coupling, nonlinearity, and large lag in its production process. Hot rolled strip products, as the main industrial material, have shown interesting potential due to their extremely high strength and excellent plasticity [1].…”
Section: Introductionmentioning
confidence: 99%
“…The steel industry, as a large-scale and complex process industry, has the characteristics of multivariate, strong coupling, nonlinearity, and large lag in its production process. Hot rolled strip products, as the main industrial material, have shown interesting potential due to their extremely high strength and excellent plasticity [1].…”
Section: Introductionmentioning
confidence: 99%